Nursing Students' Experience Using Artificial Intelligence In Nursing Care - Purnawinadi, I Gede (Poltekkes Kemenkes Banjarmasin, 2025)
The integration of Artificial Intelligence (AI) in nursing education presents both opportunities and challenges, particularly in aligning AI applications with national nursing standards. This study aimed to explore nursing students’ experiences in using AI across the nursing care process, including assessment, diagnosis, intervention, rationale development, implementation, and evaluation, as well as their perceptions of AI's alignment with the 3S books. A descriptive cross-sectional design was employed with a total of 186 nursing students recruited through purposive sampling. Data were collected using a structured questionnaire and analyzed using descriptive statistics. Findings revealed that students most frequently used AI during the assessment and diagnosis phases, while its application was limited in the implementation and evaluation stages. Furthermore, a majority perceived that AI recommendations were only partially aligned with the 3S books. These findings highlight the need for curriculum enhancement, including AI-specific training and the development of AI tools contextualized to local clinical guidelines. Clear policies, faculty readiness, and ethical considerations must be addressed to ensure safe and effective AI integration in nursing education. The study underscores the importance of institutional support in preparing nursing students to utilize AI responsibly and effectively within evidence-based and standardized frameworks.